Salus Populi Suprema Lex: A Critical Analysis of Social Jealousy In The House Renovation Process In Cimahi City - Rizal Akbar Darmawan; Dadang Sundawa; Zakir Hosen Shaikh (Jurnal Mamangan, 2023)
Home renovation  is a program  to improve the homes of residents who are less livable to become livable. In its implementation, in the process of collecting and selecting houses for people who are entitled to receive this assistance, it often requires accuracy to    get suitable prospective beneficiaries so that accuracy is needed to be right on target. This study was conducted to determine how the relationship between social jealousy conflict and the process of Home renovation assistance program in Cimahi City. The implementation of the program was carried out by the Cimahi Mobile West Java City organization in collaboration with the  Cimahi City government which was carried out in Padasuka Village, Central  Cimahi    District,  Cimahi   City. The process of building Home renovations is carried out in a participatory manner with  the  help of the surrounding community. This research was conducted with qualitative methods through a case study approach with a data collection process using observation techniques, direct  observation    in the field, and interviews with two resource persons. The results of this study are in the form of efforts to overcome social jealousy so that there is no prolonged conflict in society. For this reason, efforts that can be made in resolving conflicts in the construction of Home renovations in Cimahi City are by  conducting persuasive socialization, persuasive  in professionalism, and carrying out the culture of the surrounding area. The novelty of this research is overcoming conflict based on tolerance.